Characterization of Immunodominant BK Polyomavirus 9mer Epitope T Cell Responses. Issue 4 (17th February 2016) - Cioni, M.; Leboeuf, C.; Comoli, P.; Ginevri, F.; Hirsch, H. H.
Abstract : Uncontrolled BK polyomavirus (BKPyV) replication in kidney transplant recipients (KTRs) causes polyomavirus‐associated nephropathy and allograft loss. Reducing immunosuppression is associated with clearing viremia and nephropathy and increasing BKPyV‐specific T cell responses in most patients; however, current immunoassays have limited sensitivity, target mostly CD4 + T cells, and largely fail to predict onset and clearance of BKPyV replication. To characterize BKPyV‐specific CD8 + T cells, bioinformatics were used to predict 9mer epitopes in the early viral gene region (EVGR) presented by 14 common HLAs in Europe and North America. Thirty‐nine EVGR epitopes were experimentally confirmed by interferon‐γ enzyme‐linked immunospot assays in at least 30% of BKPyV IgG–seropositive healthy participants. Most 9mers clustered in domains, and some were presented by more than one HLA class I, as typically seen for immunodominant epitopes. Specific T cell binding using MHC class I streptamers was demonstrated for 21 of 39 (54%) epitopes. In a prospective cohort of 118 pediatric KTRs, 19 patients protected or recovering from BKPyV viremia were experimentally tested, and 13 epitopes were validated. Single HLA mismatches were not associated with viremia, suggesting that failing immune control likely involves multiple factors including maintenance immunosuppression. Combining BKPyV load and T cell assays using immunodominant epitopes may help in evaluating risk and reducing immunosuppression and may lead to safe adoptive T cell transfer. Abstract : To better characterize BK polyomavirus–specific CD8+ T cells, the authors identify 39 mostly novel immunodominant 9mer epitopes in the early viral gene region by ELISpot, CD107a, killing assay, and streptamer binding, and find that most 9mers cluster in domains, and that some are presented by more than one HLA class I.